Effect of Dupilumab on Health-Related Quality of Life and Respiratory Symptoms in Patients With COPD and Type 2 Inflammation: BOREAS and NOTUS - Bhatt, Surya P; Rabe, Klaus F; Hanania, Nicola A; Vogelmeier, Claus F; Bafadhel, Mona; Christenson, Stephanie A; Papi, Alberto; Singh, Dave; Laws, Elizabeth; Dakin, Paula; Maloney, Jennifer; Lu, Xin; et al. (Chest, 2025)
Patient-reported outcomes should be considered alongside clinical assessments to guide therapy for COPD. Does add-on dupilumab treatment improve health-related quality of life and respiratory symptoms in patients with COPD and type 2 inflammation? In this pooled analysis of two phase 3 trials, patients with COPD and type 2 inflammation receiving triple therapy were randomized 1:1 to receive dupilumab 300 mg (n = 938) or placebo (n = 936) every 2 weeks for 52 weeks. Quality of life and respiratory symptom severity were measured by change from baseline to week 52 in St. George's Respiratory Questionnaire (SGRQ; total [0-100 units, lower scores indicating better quality of life] and domain scores for symptoms, activity, and impacts) and Evaluating Respiratory Symptoms in COPD (E-RS:COPD; total [0-40 units, lower scores meaning less severe respiratory symptoms] and domain scores for breathlessness, cough and sputum, and chest symptoms) scores. In total, 1,660 patients reached week 52 (n = 830 in each treatment arm). At week 52, dupilumab vs placebo reduced SGRQ and E-RS:COPD total scores by least squares mean differences (95% CI) of -3.4 (-5.0 to -1.8; P < .0001) and -0.9 (-1.4 to -0.4; P = .0006), respectively. Similar reductions were observed across SGRQ domain scores of symptoms (-3.5 [-5.5 to -1.5]), activity (-4.0 [-5.9 to -2.1]), and impacts (-2.9 [-4.6 to -1.1]), and E-RS:COPD domain scores of breathlessness (-0.6 [-0.8 to -0.3]), cough and sputum (-0.2 [-0.3 to 0.0]), and chest symptoms (-0.1 [-0.3 to 0.0]). Dupilumab exhibited improvements in SGRQ and E-RS:COPD total and domain scores in patients with COPD and type 2 inflammation. ClinicalTrials.gov Identifiers; Numbers: NCT03930732 and NCT04456673; URL: www. gov.